Delivering authentic arts education - Dinham, Judith (South Melbourne, Victoria Cengage Learning Australia, 2023)
With a strong balance between theory and practice, Delivering Authentic Arts Education outlines the true nature of the key learning area of arts education and its importance in the curriculum, emphasising the arts as forms of creative activity, meaning-making and expression in a cultural context. Initial chapters discuss how to recognise and build on existing artistic abilities and pedagogical skills, how to encourage children's creativity, how to lead arts appreciation experiences, and the general principles of pedagogies, planning and assessment. Part 1 ends with an example unit of Inquiry Programming: Patterns around us. Part 2 specifically examines the five arts areas: dance, drama, media arts, music and visual arts.
Includes bibliographical references and index.
Keywords: Art -- Study and teaching (Higher) -- Australia; Art teachers -- Training of -- Australia; Student teachers -- Australia